Characteristics of juvenile chum salmon Oncorhynchus keta and pink salmon O. gorbuscha in hatchery reproduction in the Margaritovka River basin (central Primorye) - I. S. Manzaeva; O. V. Zelennikov (Известия ТИНРО, 2025)
Juveniles of chum salmon Oncorhynchus keta and pink salmon O. gorbuscha reared at Pfusung fish hatchery in the Margaritovka River basin (central Primorye) are investigated. The chum salmon eggs were incubated from the breeders of local stock between September 30 and November 7, fed in cages installed in the riverbed between February 26 and April 15, and were released into the wild in amount of 7.665.106 ind. between April 11 and May 15 with the body weight of 895–1100 mg. Over the entire rearing period from start of incubation to release, the juvenile chum salmon had accumulated 1103.7 degree-days of heat, on average. The pink salmon embryos were transported to the hatchery from southeastern Sakhalin immediately before hatching, with the heat accumulation of 501.8 degree-days. Their feeding began on February 26. These fish were released on April 11, after the total accumulation of 1335.9 degree-days of heat. Histological control of cardiac and pyloric sections of stomach, mid-gut and spiral valve, liver and gonads development was conducted for both species during the period from hatching to release. Consistent changes in functional activity of the gastric glands and digestive epithelial cells were detected, with increasing the number of mucus cells in the intestines of fry. Differences in fat content in the liver were noted between age groups.